The Influence of Subclinical Hypothyroidism on Endocrine and Metabolic Characteristics in Patients with Polycystic Ovary Syndrome - Dai F; Wu Z; Qin S; Wu F; Wang M; Liu X; Liu F (International Journal of Women's Health)
Fang Dai,1,* Zijian Wu,2,* Shuai Qin,1 Fang Wu,3 Mingqiang Wang,4 Xiangxiu Liu,1 Fen Liu1 1Department of Endocrinology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, People’s Republic of China; 2Department of Brain surgery, The Second People’s Hospital of Guizhou Province, Guiyang, People’s Republic of China; 3Department of Obstetrics, The First People’s Hospital of Guizhou Province, Guiyang, People’s Republic of China; 4Teaching Evaluation Center, Guizhou University of Traditional Chinese Medicine, Guiyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Dai, Department of Endocrinology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, No. 71 Baoshan North Road, Guiyang, Guizhou, 550001, People’s Republic of China, Email 13765063256@163.comObjective: To analyze the influence of subclinical hypothyroidism (SCH) on endocrine and metabolic characteristics in patients with polycystic ovary syndrome (PCOS).Methods: A total of 198 cases of PCOS patients admitted to our hospital from January 2022 to December 2023 were selected for the study. According to the presence or absence of SCH, patients were divided into the SCH group (n = 40) and the non-SCH group (n = 158). Differences in demographic characteristics, thyroid hormones, sex hormones, and glucose and lipid metabolism were analyzed between the two groups. Additionally, the correlation between SCH and various endocrine and metabolic indicators in PCOS patients was assessed.Results: There was no statistically significant difference in demographic characteristics between the two groups (P > 0.05). Compared to the non-SCH group, the SCH group had significantly higher levels of serum luteinizing hormone (LH), prolactin (PRL), triglycerides (TG), total cholesterol (TC), fasting insulin (FINS), and homeostasis model assessment of insulin resistance (HOMA-IR) (P < 0.05), Conversely, the SCH group had significantly lower levels of serum follicle-stimulating hormone (FSH), estradiol (E2), thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) (P < 0.05). Correlation analysis indicated that LH, FSH, E2, PRL, TSH, TG, TC, FINS, HOMA-IR were positively correlated with PCOS complicated by SCH, while FT3, FT4 were negatively correlated.Conclusion: SCH in PCOS patients is associated with endocrine and metabolic dysfunction, primarily affecting thyroid hormone levels, sex hormones, and glucose and lipid metabolism. Assessing thyroid function is essential for the comprehensive evaluation and management of PCOS patients.Keywords: subclinical hypothyroidism, polycystic ovary syndrome, endocrine, metabolic characteristics